Achilles' Heel: a story map - Smith, Georgina; Graziosi, Ignazio; Parker, Louis; Wyckhuys, Kris A.G. (2015)
A story about the vital importance of cassava in Southeast Asia, and the many risks this “Rambo root” faces from pest and disease outbreaks.